A general protocol for the efficient synthesis of polyarylated benzenes by multiple Suzuki-Miyaura reactions of polychlorinated benzenes. Issue 8 (25th February 2016) - Reimann, Sebastian; Ehlers, Peter; Sharif, Muhammad; Spannenberg, Anke; Langer, Peter
Abstract: A general protocol for the highly efficient synthesis of polyarylated benzene derivatives by multiple Suzuki-Miyaura reactions of polychlorinated benzenes was developed. Using bulky and electron-rich phosphine ligands, up to quantitative yields of the desired compounds were achieved. Moreover, the reactions show good functional group tolerance and allow the employment of sterically demanding boronic acids. Graphical abstract: